THE EVALUATION ON THE AVAILABILITY AND THE NEEDS OF WATER FROM ULEE GLEE IRRIGATION OF PIDIE REGENCY OF NANGGROE ACEH DARUSSALAM - (NIM 95005313), Muzakkir
ABSTRACT: The irrigation area of Ulee glee with its potential area of 3000 ha currently obtain its water supply from the Meureudu and Jeulanga river. This area is located at the peak of Bukit Barisan mountain, called Ge Loyang, whose the elevation is 1865 m above the sea level. The water supply from Meureudu and Jeulanga river has been using the continuous flow system to meet the water needs of as much as 0,986 m3/second for the area of 1485 ha and 0,980 m3/second for the area of 1515 ha. The reliable water discharge was calculated on the basis of the rainfall data recorded by the Meureudu and Pantaredja stations. The calculation used F.J. Mock method. The analysis showed that the monthly reliable water discharge for Jeulanga river was between 0,142 m3/second and 2,864 m3/second whereas for Meuruedu river the reliable water supply was between 1,014 m3/second and 20,290 m3/second. The needs of irrigation water is influenced by land availability, plant consumption, percolation, the alteration of water coat, effective rain, and irrigation efficiency. The needs of irrigation water were calculated by using the equation of Van De Goor and Ziljstra. The data for the calculation were obtained from the biggest water needs of as much as 1,416 l/second/ha during the land preparation and 1,047 l/second/ha during the cultivation and harvest period. Based on the study about the water availability and needs in the area surrounding the Ulee Glee irrigation of Pidie Regency, it can be concluded that the water availability was sufficient and the area function could be increased up to 3000 ha. It was found that the cultivation intensity with cropping intensity (CI) of 300percent was three times per year with such cultivation patterns as MT I Paddy, MT II Paddy, and MT III non staple food crops (Palawija). The most profitable cultivation was from the beginning of October to the end of September. It is recommended that the local regent issue a decree concerning the cultivation patterns and schedules to achieve the optimum cropping intensity.